Unveiling Cultural Richness In Asy-Sya’ir Novel's Values - Budiono, Budiono; Kisyani, Kisyani; Shodiq, Samsul (Universitas Muhammadiyah Gorontalo, 2023)
The objective of this research is to analyze the cultural values depicted in the novel Asy-sya’ir by Mustafa Lutfi al-Manfaluti. The primary data source employed in this study was the Arabic edition of the novel, which was published in the year 1912. The study employed a descriptive-analytic research approach. The cultural values depicted in the piece of art were analyzed and categorized based on the cited theory using a systematic approach involving careful and repeated reading. The analysis of the data was conducted by applying Alessandro Duranti's theory of cultural values, resulting in the derivation of the findings. The findings indicate that the Asy-sya’ir novel, a literary rendition of the French classic Cyrano de Bergerac, depicts the author's poignant tale of love and incorporates a multitude of cultural values that are unique to the society in which it originated. The investigation has identified six discrete cultural values: cultural value as an intrinsic distinguishing element, cultural value as a reservoir of knowledge, cultural value as a medium of expression, cultural value as a utilitarian framework, cultural value as a form of intermediary, and cultural value associated with religious viewpoints on the divine.